High‐production dairy cattle exhibit different rumen and fecal bacterial community and rumen metabolite profile than low‐production cattle. Issue 4 (11th September 2018) - Mu, Yingyu; Lin, Xueyan; Wang, Zhonghua; Hou, Qiuling; Wang, Yun; Hu, Zhiyong
Abstract: Our aim was to simultaneously investigate the gut bacteria typical characteristic and conduct rumen metabolites profiling of high production dairy cows when compared to low‐production dairy cows. The bacterial differences in rumen fluid and feces were identified by 16S rDNA gene sequencing. The metabolite differences were identified by metabolomics profiling with liquid chromatography mass spectrometry (LC‐MS). The results indicated that the high‐production dairy cows presented a lower rumen bacterial richness and species evenness when compared to low‐production dairy cows. At the phylum level, the high‐production cows increased the abundance of Proteobacteria and decreased the abundance of Bacteroidetes, SR1, Verrucomicrobia, Euryarchaeota, Planctomycetes, Synergistetes, and Chloroflexi significantly ( p  < 0.05). At the genus level, the rumen fluid of the high‐production group was significantly enriched for Butyrivibrio, Lachnospira, and Dialister ( p  < 0.05). Meanwhile, rumen fluid of high‐production group was depleted for Prevotella, Succiniclasticum, Ruminococcu, Coprococcus, YRC22, CF231, 02d06, Anaeroplasma, Selenomonas, and Ruminobacter significantly ( p  < 0.05). A total of 92 discriminant metabolites were identified between high‐production cows and low‐production cows. Compared to rumen fluid of low‐production dairy cows, 10 differential metabolites were found up‐regulated in rumen fluid of high‐production dairy cows, including 6alpha‐Fluoropregn‐4‐ene‐3, 20‐dione, 3‐Octaprenyl‐4‐hydroxybenzoate, disopyramide, compound III(S), 1, 2‐Dimyristyl‐sn‐glycerol, 7, 10, 13, 16‐Docosatetraenoic acid, ferrous lactate, 6‐Deoxyerythronolide B, vitamin D2, L‐Olivosyl‐oleandolide. The remaining differential metabolites were found down‐regulated obviously in high‐production cows. Metabolic pathway analyses indicated that most increased abundances of rumen fluid metabolites of high‐yield cows were related to metabolic pathways involving biosynthesis of unsaturated fatty acids, steroid biosynthesis, ubiquinone and other terpenoid‐quinone biosynthesis. Most down‐regulated metabolic pathways were relevant to nucleotide metabolism, energy metabolism, lipid metabolism and biosynthesis of some antibiotics. Abstract : Our aim was to simultaneously investigated the gut bacteria typical characteristic and conduct rumen metabolites profiling of high‐production dairy cows when compared to low‐production dairy cows. The aim of the study was to explore the typical gut bacteria and rumen typical metabolites matter of high‐production airy cows. After that, the results can be applied in the low‐yield dairy cows to improve their milking performance.